AKTIVITAS ANTIFUNGI EKSTRAK METANOL DAUN SALAM (Syzygium polyanthum [Wight] Walp.) TERHADAP PERTUMBUHAN Malassezia sp. (M1) SECARA IN VITRO - Sulistrioningsih, Sulistrioningsih; Wardoyo, Elvi Rusmiyanto Pancaning; Kurniatuhadi, Rikhsan (Jurnal Protobiont, 2020)
Malassezia sp. is a normal flora on the skin of humans and animals. A considerable amount of the fungus may cause tinea versicolor and dandruff. One of the plants that is known to have antifungal compounds is bay leaf (Syzygium polyanthum [Wight] Walp.). This research was done to determine the ability and the Minimum Inhibitory Concentration (MIC) of methanol extract from bay leaves S. polyanthum in inhibiting the growth of Malassezia sp. (M1). This study used a completely randomized design (CRD) withÂ  treatment levels that consisted of concentrations of 80%, 90%, and 100%, negative control (sterile distilled water) and positive control (ketoconazole 2%). The antifungal activity test was carried out using the Kirby-Bauer method. The data showed that each treatment levels had different results. Concentrations of 90% and 100%, and positive control showed inhibition zones of 9.27 mm, 11.57 mm, and 16.67 mm, respectively. Therefore the concentration of 90% was the Minimum Inhibitory Concentration (MIC) of methanol extract from bay leaves S. polyanthum against the growth of Malassezia sp. (M1).